Sound harmony and its evolution in foreign Turkic studies - Samatov, I.; Akimisheva, Zh.A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The concept of sound harmony, including both vowel and consonant harmony, has long been a defining phonological feature of Turkic languages. This characteristic, deeply rooted in the history of these languages, attracted the attention of foreign scholars as early as the 19th century. Initial studies focused on vowel harmony, recognizing it as a systematic and unique trait. Over time, as interest in Turkic phonology grew, researchers expanded their scope to include consonant harmony and its significance. The article explores the phenomenon of sound harmony, analyzing its evolution within foreign studies on Turkic languages. It highlights sound harmony as a universal linguistic model, reflecting both stereotypical and national features across diverse Turkic languages. The study emphasizes the cognitive and structural dimensions of sound harmony, investigating its phonetic, structural, and semantic patterns. Using structural-semantic modeling, the article traces the consistency of sound harmony in modern Turkic languages and its role in broader phonological frameworks. Drawing on works by scholars like Gerard Clauson, William Schmalstieg, and Karlene Kenyon, the article delves into the historical development, phonological systems, and morphological implications of sound harmony. It underscores its enduring influence on the linguistic and cultural identity of Turkic peoples, shaped by phonetic, diachronic, and cultural factors.